Systemic Fibroinflammatory Disorders - Vaglio, Augusto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides detailed information on the nosology, pathology, pathogenesis, clinical presentation, diagnosis and treatment of fibro-inflammatory disorders, rare diseases that often display systemic organ involvement. Among the conditions considered are IgG4-related disease, sclerosing cholangitis, Hashimoto$1 (Bs and Riedel$1 (Bs thyroiditis, retroperitoneal fibrosis/chronic periaortitis, mediastinal fibrosis, Erdheim-Chester disease, gadolinium-induced fibrosis, and sclerosing mesenteritis. This group of entities is still poorly defined and is characterized by the common denominator of chronic inflammatory infiltrate admixed with abundant fibrosis. IgG4-related disease is the prototypical example. Systemic Fibroinflammatory Disorders is the first book to draw together information on these conditions. As these diseases often require an interdisciplinary approach, the book is addressed to specialists of different disciplines, especially internists, rheumatologists, nephrologists, clinical immunologists, and hematologists.s
Preface -- 1 Genetics of fibro-inflammatory disorders -- 2 Basic mechanisms linking inflammation and fibrosis -- 3 Histopathology of systemic fibro-inflammatory disorders -- 4 IgG4-related disorders: clinical and therapeutic aspects -- 5 IgG4-related disorders: pathophysiology -- 6 IgG4-related nephropathy -- 7 Autoimmune (IgG4-related) pancreatitis and sclerosing cholangitis -- 8 Sclerosing forms of autoimmune thyroiditis: from Hashimoto$1 (Bs to Riedel$1 (Bs to IgG4-related forms -- 9 Chronic periaortitis/retroperitoneal fibrosis: overview -- 10 Diffuse periaortitis -- 11 Treatment of chronic periaortitis/retroperitoneal fibrosis -- 12 Mediastinal fibrosis -- 13 Erdheim-Chester disease -- 14 Nephrogenic systemic fibrosis -- 15 Sclerosing mesenteritis -- 16 Malignant diseases mimicking retroperitoneal fibrosing disorders -- Subject Index.s
Keywords: Medicine; Immunology; Nephrology; Rheumatology; Medicine & Public Health; Rheumatology; Immunology; Nephrology